How Does the FDA Address Cybersecurity in AI Devices? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The integration of Artificial Intelligence (AI) and Machine Learning (ML) into medical devices is revolutionizing healthcare, offering unprecedented opportun...
Keywords: FDA Regulation and Compliance; Address; Cybersecurity; Devices; Artificial Intelligence; Machine Learning; Healthcare